2014
DOI: 10.1007/s00253-014-6153-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rumen microbiome of Indian Kankrej cattle (Bos indicus) adapted to different forage diet

Abstract: Present study described rumen microbiome of Indian cattle (Kankrej breed) to better understand the microbial diversity and largely unknown functional capacity of the rumen microbiome under different dietary treatments. Kankrej cattle were gradually adapted to a high-forage diet (four animals with dry forage and four with green forage) containing 50 % (K1), 75 % (K2) to 100 % (K3) forage, and remaining concentrate diet, each for 6 weeks followed by analysis of rumen fiber adherent and fiber-free metagenomic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 46 publications
8
19
1
1
Order By: Relevance
“…Studies that decipher the community composition of anaerobic sludge has also been conducted by many research groups across the world (Guo et al, 2015; Sun et al, 2015; Ferrentino et al, 2016; Ju et al, 2016) but the studies conducting the detailed investigation of taxonomic as well as functional composition of pre- and post-treated anaerobic sludge are very few. Researchers have used different sequencing depths ranging from 0.1 GB to 3.3 GB to study functional composition using the Ion-torrent platform (Joshi et al, 2014; Patel et al, 2014; Rua et al, 2015; Hinsu et al, 2017; Motooka et al, 2017). Here, we employed ∼1 GB sequencing depth for shotgun metagenomic sequencing to inspect the microbial shifts in pre- and post-treated sludge along with their functional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that decipher the community composition of anaerobic sludge has also been conducted by many research groups across the world (Guo et al, 2015; Sun et al, 2015; Ferrentino et al, 2016; Ju et al, 2016) but the studies conducting the detailed investigation of taxonomic as well as functional composition of pre- and post-treated anaerobic sludge are very few. Researchers have used different sequencing depths ranging from 0.1 GB to 3.3 GB to study functional composition using the Ion-torrent platform (Joshi et al, 2014; Patel et al, 2014; Rua et al, 2015; Hinsu et al, 2017; Motooka et al, 2017). Here, we employed ∼1 GB sequencing depth for shotgun metagenomic sequencing to inspect the microbial shifts in pre- and post-treated sludge along with their functional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously characterized rumen microbiome of Kankrej cattle, Jaffrabadi and Mehsani buffalo fed with different roughage concentrations in the diet using amplicon and shotgun sequencing and demonstrated that bacterial community in the liquid and solid fractions of rumen are diverse and different proportions of roughage in the diet exerted significant impact on rumen bacterial population [42,45,48,53]. In the present study we further hypothesised that the importance of the role of bacterial species in the rumen is not only determine by their abundance but how functionally active they are.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic sequencing represents a powerful alternative to ribosomal RNA (rRNA) sequencing for analyzing complex microbial communities [9], and this method avoids the need to culture individual microorganisms and eliminates cloning and polymerase chain reaction (PCR) biases [10]. Recently, Patel et al [11] found that diet proportion, fraction of rumen, and forage type affected rumen microbiome of Indian Kankrej cattle at taxonomic as well as functional levels by metagenomic sequencing. According to metagenomic analysis results, Zhu et al [6] found that ~37-Mbp contig sequences from gut microbes of the giant panda recovered putative genes coding cellulose-digesting related enzymes in Clostridium group I, showing that the giant pandas had evolved a number of traits to overcome the anatomical and physiological challenge of digesting a diet high in fibrous matter.…”
Section: Introductionmentioning
confidence: 99%